2011
DOI: 10.1007/s00705-011-1115-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lassa virus and Ebola virus infection in host cells treated with the kinase inhibitors genistein and tyrphostin

Abstract: Arenaviruses and filoviruses are capable of causing hemorrhagic fever syndrome in humans. Limited therapeutic and/or prophylactic options are available for humans suffering from viral hemorrhagic fever. In this report, we demonstrate that pre-treatment of host cells with the kinase inhibitors genistein and tyrphostin AG1478 leads to inhibition of infection or transduction in cells infected with Ebola virus, Marburg virus, and Lassa virus. In all, the results demonstrate that a kinase inhibitor cocktail consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…These results would suggest that in BHK-21 cells JUNV uses a different receptor that is internalized by an EIPA-sensitive endocytic pathway that may involve activation of the receptor tyrosine kinases TIM or TAM, or both, as has been proposed for several other enveloped viruses (56). Accordingly, broad-range protein kinase inhibitors like staurosporine and genistein are able to inhibit viral cell entry mediated by macropinocytois (84), and genistein treatment was shown to inhibit both LASV (85) and Pichinde virus (86) infections. NHE3 was also identified in the same siRNA screen as a host cell factor required for efficient multiplication of VSV in HeLa cells (22).…”
Section: Discussionmentioning
confidence: 72%
“…These results would suggest that in BHK-21 cells JUNV uses a different receptor that is internalized by an EIPA-sensitive endocytic pathway that may involve activation of the receptor tyrosine kinases TIM or TAM, or both, as has been proposed for several other enveloped viruses (56). Accordingly, broad-range protein kinase inhibitors like staurosporine and genistein are able to inhibit viral cell entry mediated by macropinocytois (84), and genistein treatment was shown to inhibit both LASV (85) and Pichinde virus (86) infections. NHE3 was also identified in the same siRNA screen as a host cell factor required for efficient multiplication of VSV in HeLa cells (22).…”
Section: Discussionmentioning
confidence: 72%
“…To our knowledge, small molecules targeting the viral PPxYhost Nedd4 interaction have not been reported; however, a number of previous studies have reported on antivirals targeting virushost interactions and/or budding of filoviruses, arenaviruses, rhabdoviruses, and others (7,9,12,31,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). Host Tsg101 and its recruitment by viral PTAP type L domains of RNA viruses have been targeted for the development of antivirals in a number of recent studies (7,9,31,39,71,(82)(83)(84)(85)(86)(87)(88).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular target is not known, CMLDBU3402 (25) exhibited broad spectrum activity against a number of non-segmented single RNA viruses including EBOV and inhibited RNA transcription in EBOV (Filone et al, 2013). Other compounds, which were shown to have activity against Ebola virus include antioxidants , selective estrogen receptor modulators (Johansen et al, 2013), cell cycle inhibitors and kinase inhibitors (Kolokoltsov et al, 2012).…”
Section: Other Potential Targets and Miscellaneous Compounds With Actmentioning
confidence: 97%